Climate Change Extremes and Photovoltaic Power Output - Cordero-Carrasco, R; Christin-Feron, S (Nature Research, 2021)
Sustainable development requires climate change mitigation and thereby a fast energy transition to renewables. However, climate change may affect renewable power outputs by enhancing the weather variability and making extreme conditions more frequent. High temperature or clouds, for example, can lead to poorer photovoltaic (PV) power outputs. Here, we assess global changes in the frequency of warm and cloudy conditions that lead to very low PV power outputs. Using simulations from global climate models (RCP4.5 and RCP8.5), we show that summer days with very low PV power outputs are expected to double in the Arabian Peninsula by mid-century but could be reduced by half in southern Europe over the same period, even under a moderate-emission scenario. Changes for winter, either enhancing or mitigating the PV power intermittency, are projected to be less striking, at least in low- and mid-latitude regions. Our results present valuable information for energy planners to compensate for the effects of future weather variability. © 2020, The Author(s), under exclusive licence to Springer Nature Limited.